ANALISIS RISIKO DAN PENENTUAN PRIORITAS MITIGASI ASET TEKNOLOGI INFORMASI PADA KOPERASI MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING - Wahdana, Aldi; Asrianda; Fikry, Muhammad (Journal of Information Technology, 2026)
This study aims to analyze risks and determine mitigation priorities for information technology assets at the Melati Civil Servant Cooperative. The Simple Additive Weighting (SAW) method is used to determine mitigation priorities based on four main criteria: risk level, asset criticality, Return on Investment (ROI), and Total Cost of Ownership (TCO). This study involved eight information technology assets used to support the cooperative's daily operational activities. Research data was obtained through structured interviews with cooperative administrators to assess the probability and impact of possible risks, the criticality level of each asset, the cost of asset ownership during its useful life, and the resulting economic benefits. The obtained data was then processed using the SAW method to generate a preference value for each asset. The analysis results show that the Savings and Loans Data asset received the highest preference value of 0.876, making it the main mitigation priority. Furthermore, the Cooperative Member Data and Backup Storage Device assets were ranked next in priority. Based on these results, it can be concluded that the SAW method is able to assist cooperative administrators in determining risk mitigation priorities for information technology assets objectively and efficiently